Johnny Tremain : a novel for old & young - Forbes, Esther; Ward, Lynd. 1905-1985 (Boston : Houghton Mifflin, 1943)
After injuring his hand, a silversmith's apprentice in Boston becomes a messenger for the Sons of Liberty in the days before the American Revolution.
Keywords: United States -- History -- Revolution 17751783 -- Juvenile fiction